2021
DOI: 10.3389/fonc.2021.761979
|View full text |Cite|
|
Sign up to set email alerts
|

Positive Reciprocal Feedback of lncRNA ZEB1-AS1 and HIF-1α Contributes to Hypoxia-Promoted Tumorigenesis and Metastasis of Pancreatic Cancer

Abstract: BackgroundMany studies have reported the roles of the extracellular hypoxia microenvironment in the tumorigenesis and metastasis of multiple cancers. However, long noncoding RNAs (lncRNAs) that induce cancer oncogenicity and metastasis of pancreatic cancer (PC) under hypoxia conditions remain unclear.MethodsIn PC cells, the expression levels of lncRNAs in different conditions (normoxia or hypoxia) were compared through RNA sequencing (RNA-seq). The effects of the zinc finger E-box-binding homeobox 1 (ZEB1-AS1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…In published research, the lncRNA ZEB1-AS1 was considered to be tightly related to the onset and progression of many types of cancers. According to Jin’s research, the positive reciprocal looping of HIF-1/ZEB1-AS1/ZEB1/HDAC1 leads to hypoxia-induced oncogenicity and PC metastasis ( Jin et al, 2021 ). Siena confirmed that lncRNA ZEB1-AS1 can influence the invasiveness and phenotypic transformation of melanoma through epithelial to mesenchymal transition (EMT) ( Siena et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In published research, the lncRNA ZEB1-AS1 was considered to be tightly related to the onset and progression of many types of cancers. According to Jin’s research, the positive reciprocal looping of HIF-1/ZEB1-AS1/ZEB1/HDAC1 leads to hypoxia-induced oncogenicity and PC metastasis ( Jin et al, 2021 ). Siena confirmed that lncRNA ZEB1-AS1 can influence the invasiveness and phenotypic transformation of melanoma through epithelial to mesenchymal transition (EMT) ( Siena et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ZEB1-AS1 scaffolded the interaction of HIF-1α, ZEB1, and HDAC1, leading to deacetylation and stabilization of HIF-1α protein, thus forming a positive feedback loop. Knockdown of ZEB1-AS1 inhibited progression and metastasis of pancreatic cancer in nude mice (Jin et al, 2021).…”
Section: Regulation Of Nat Expressionmentioning
confidence: 98%
“…Furthermore, lncRNA-nuclear transport factor 2 pseudogene 3 (NUTF2P3)-001 increased Ki-ras2 Kirsten rat sarcoma viral oncogene homolog (KRAS) expression by overcoming the suppression of KRAS via miR-3923 in PC cells 16 . Additionally, under hypoxic conditions, ZEB1-AS1 increased the transcription of ZEB1 and stabilised HIF-1α in PC cells 17 . However, the crucial function of lncRNAs needs to be understood to identify latent mechanisms and improve potential therapeutic strategies for patients with PC.…”
Section: Introductionmentioning
confidence: 93%
“…The chromatin immunoprecipitation (ChIP) analysis was conducted using Abcam's ChIP Kit (catalogue# ab500) and anti-HIF-1α (1:1,000, catalogue#ab51608) antibody as per the manufacturer's instructions 16,17 . Rabbit IgG (catalogue # ab172730; Abcam) was used as the control.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%